1998
DOI: 10.1007/bf02467654
|View full text |Cite
|
Sign up to set email alerts
|

Crown ether capped cyclodextrin used as stationary phase for capillary gas chromatography

Abstract: SummaryThe solution of a new synthesized compound, mono-6-(l'-benzo-aza-15-crown-5)-2, 3, 6-permethyl-13-cyclodextrin, in the moderately polar polysiloxane OV-1701 was coated onto fused silica capillary column. The chromatographic characteristics including column efficiency, polarity and selectivity were studied. Excellent selectivity for the separation of enantiomers and positional isomers was obtained. The results show that the combined effect between the special caves of [3-cyclodextrin and crown ether play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…After collection by filtration, the crude product was purified by column chromatography on Sephadex G-25 with distilled, deionized water as eluent to give a pure sample (0.50 g, yield 18%). Mp 240 °C (dec.); 1 H NMR (D 2 O, 300 MHz, TMS, ppm):  2.0-3.0 (m, 11H), 3.0-4.0 (m, 58 H), 4.1 (m, 2H), 4.9 (m, 7 H), 6…”
Section: Synthesis Of N-(benzoaza-15-crown-5)-acylaminomethylene Teth...mentioning
confidence: 99%
See 1 more Smart Citation
“…After collection by filtration, the crude product was purified by column chromatography on Sephadex G-25 with distilled, deionized water as eluent to give a pure sample (0.50 g, yield 18%). Mp 240 °C (dec.); 1 H NMR (D 2 O, 300 MHz, TMS, ppm):  2.0-3.0 (m, 11H), 3.0-4.0 (m, 58 H), 4.1 (m, 2H), 4.9 (m, 7 H), 6…”
Section: Synthesis Of N-(benzoaza-15-crown-5)-acylaminomethylene Teth...mentioning
confidence: 99%
“…1 Recently, many approaches to appropriately introduce another recognition site, such as a CyD, calixarene or crown ether, to the parent CyD rim have been widely reported. [2][3][4][5][6][7][8] For example, it was reported that crown ether capped -CyDs can mimic the receptor sites of enzymes, 5c and thus successfully be used as artificial enzyme-mimetic systems to accelerate the hydrolysis of p-nitrophenyl ester in the presence of transition metal cations 9 or as stationary-phase selector for chromatography showing excellent enantioselectivity. 10 Moreover, Suzuki et al reported the strong binding of tryptophan by crown ether-tethered CyDs owing to the superiority of the CyD secondary-hydroxyl side modification.…”
Section: Introductionmentioning
confidence: 99%
“…Another option is to examine a more orthogonal chromatographic approach [16,17] which may include chiral chromatography either in reversed or normal-phase mode and using either a chiral mobile phase additive (CMPA) [18] or a CSP [19][20][21][22][23]. Furthermore, an orthogonal analytical technique may also be utilized and positional isomer separations have been reported using capillary electrophoresis (CE) [19,24], capillary electrochromatography [25], supercritical fluid chromatography [26] and gas chromatography [27]. Capillary electrophoresis, where the separation mechanism is truly orthogonal to that of reversedphase chromatography, can also be very effective in separating isomers, both optical or positional, when a chiral medium is employed in the background electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that crown ether-capped b-CDs [15 ± 17] exhibited high binding constants for several guest molecules due to the cooperation of the b-CD and the crown ether. Although crown ether capped b-CD has already been used to model the receptor sites of enzymes for a long time [16], its use as a stationary-phase selector for chromatography has seldom been studied [18]. It was reported that benzo-aza-15-crown-5 capped b-CD used as stationary phase in GC showed excellent enantioselectivity [18].…”
mentioning
confidence: 99%
“…Although crown ether capped b-CD has already been used to model the receptor sites of enzymes for a long time [16], its use as a stationary-phase selector for chromatography has seldom been studied [18]. It was reported that benzo-aza-15-crown-5 capped b-CD used as stationary phase in GC showed excellent enantioselectivity [18]. Recently, it was shown that combination of a crown ether and b-CD as CE additive sometimes produce better enantiomer separation than did either selector alone [9] [19] [20].…”
mentioning
confidence: 99%